Keefektifan Layanan Bimbingan Klasikal Teknik Project Based Learning Untuk Meningkatkan Literasi Kesehatan Mental Pada Siswa Kelas XII Di SMA N 1 Boja - Bernadin Anindya Ramadhani; Tri Suyati; Venty Venty (Departement of Mathematics Education, 2024)
This research is motivated by the low knowledge of students about mental disorders and their problems, the lack of student skills in controlling emotions experienced, students are less able to socialize with peers. This study aims to determine the effectiveness of classical guidance services with project-based learning techniques to improve mental health literacy of XII grade students at SMA N 1 Boja. This research uses a quantitative method pretest-posttest control group design. The sample used cluster random sampling technique with 70 students from 350 population. The validity test uses a correlation test with product moment. The number of statement items consisted of 40 items, which were then tested on 30 respondents resulting in 22 valid items and 18 invalid items. The data analysis technique uses the N-Gain hypothesis, and the independent sample T-test. The results of the study prove that there is an increase in student knowledge at SMA N 1 Boja, as evidenced by the results of the N-Gain hypothesis test obtained by the calculation of 64.7% included in the category quite effective. And the independent sample T-test test obtained Sig. (2-tailed) 0.000 <0.05, it shows that Ha is accepted, namely “Classical guidance services using project-based learning techniques are effective for increasing the mental health literacy of XII grade students at SMA N 1 Boja.”